PEMANFAATAN ASAP CAIR LIMBAH GERGAJIAN KAYU PINUS SEBAGAI BIOPESTISIDA DALAM MENGHAMBAT SERANGAN HAMA PENGGEREK BUAH KOPI (Hypothenemus hampei Ferr.): Utilization of Liquid Smoke from Pine Wood in Inhibiting the Attacks of Coffe Fruit Press (Hypothenemus hampei Ferr.) - Hadiyane, Anne; Navila, Aviva; Karliati, Tati; Pari, Gustan; Darmawan, Saptadi; Rumidatul, Alfi (Jurnal Penelitian Hasil Hutan, 2024)
Sawmill waste is a waste product that needs to be put to use. Applying biorefinery principles through pyrolysis technology, which produces liquid smoke, is one of the innovative efforts to utilize sawmill waste. Chemical compounds contained in the liquid smoke have the potential to act as biopesticides. Therefore, this study aimed to test the ability of liquid smoke from pine sawmill waste to fight PBKo (Hypothenemus hampei) pests on coffee plants. Pyrolysis produced the liquid smoke at 400–450 °C for 4–7 hours. The observed parameters were the physicochemical characteristics and efficacy of liquid smoke biopesticides at concentrations of 1.5%, 2%, and 2.5% against PBKo pests through pest attack tests, toxicity tests, and repellency tests. The results showed a total phenol value of 7248.01 mg GAE/100g. The results of the GC-MS analysis of the liquid smoke, which has the potential to be an insecticidal compound toxic to coffee fruit borer pests, are acetic acid, phenol, alcohol, furan, cycloalkane, cyclohexane, alkene, eugenol, and guaiacyl acetone. Based on the stydy’s results, liquid smoke from sawn pine wood waste at a concentration of 2.5% has the potential to be a natural biopesticide for inhibiting the growth of PBKo pests on coffee plants.